Political Reform Reconsidered The Trajectory of a Transformed Japanese State - Machidori, Satoshi (Springer Nature Singapore : Imprint: Springer, 2023)
This Open Access book provides a comprehensive analysis of political reforms in Japan since the 1990s, emphasizing the role of ideas in shaping their goals and outcomes. For more than fifteen years following the collapse of Japan's economic bubble, politicians, business people and academics tackled a range of institutional reforms. The sweeping changes they enacted-covering almost all facets of the public sphere, including elections, public administration, courts and the central bank-fundamentally altered Japanese political processes and policies. Taken together, they arguably represent the final touches of Japan's political modernization, which had been unfolding since the mid-19th century. Throughout the reform process, advocates were inspired by a combination of liberal and modernist ideas. This book examines those guiding concepts and illustrates the often messy process of applying them to real-world institutions. While most reforms began from common goals, they ultimately produced different-and frequently unexpected-institutional outcomes, which continue to shape Japanese politics. By focusing on the relationship between the ideas and processes that shaped Japan's reforms, this book presents a broad vision of institutional change in comparative politics. The author of the book Satoshi Machidori is professor of political science at the Graduate School of Law, Kyoto University. The translator and author of the afterword, Tobias S. Harris is Deputy Director of the Asia Program at German Marshall Fund of the United States.